Restructuring Wet Age-Related Macular Degeneration Services During the COVID-19 Pandemic to Allow Social Distancing Outpatient Clinics (SDOC) - Groppe M; Bindra MS (Clinical Ophthalmology, 2021)
Markus Groppe,* Mandeep Singh Bindra* Retina Unit, Buckinghamshire Healthcare NHS Trust, Stoke Mandeville and Amersham Hospital, Aylesbury, HP21 8AL, UK*These authors contributed equally to this workCorrespondence: Markus GroppeRetina Unit, Buckinghamshire Healthcare NHS Trust, Stoke Mandeville and Amersham Hospital, Aylesbury, HP21 8AL, UKEmail markus.groppe@nhs.netBackground: COVID-19 has had a major impact on health-care provision. Social distancing will impact the organization of outpatient clinics (OCs) and require general restructuring of health care.Methods: Our retinal team participated in a structured fact-finding session to implement social distancing of patients and staff in wet age-related macular degeneration (wAMD) clinics. Clinic flow and performance were continually reviewed and improved. A retrospective audit of all wAMD follow-up appointments was conducted for 4 weeks from the start of the UK lockdown. A search for clinical guidance regarding retinal services was performed on the homepages of international professional bodies. The guidelines were compared to the implemented changes in our wAMD social distancing OCs (SDOCs) and potential risk examined.Results: The changes in clinic setup to achieve SDOCs are described. The average total time spent in the clinic area by each patient has reduced by 27%. The audit concluded that 65% of patients needed a treatment interval of 4– 7 weeks after their appointment, 17% at either 8 or 9 weeks, and 18% at 10 weeks or beyond. The UK, Australian–New Zealand, US, and German professional ophthalmology bodies have published divergent guidelines, but all recommended a continuation of anti-VEGF injections.Conclusion: Health-care provision will change and hospitals and outpatient facilities will have to adapt to the COVID-19 epidemic. We describe a clinic setup (SDOCs) that minimizes risk to patients and staff, while maintaining the ability to treat each patient and their disease individually.Keywords: age-related macular degeneration, COVID-19, social distancing, SDOC